The Double-Edged Sword Effect of Relational Crafting on Job Well-Being - Li, Shanshan; Meng, Bin; Wang, Qingjin (Frontiers in Psychology, 2022)
Is relational crafting always beneficial? Despite the increasing research on the positive outcomes of relational crafting, some evidence still indicates its dysfunctional consequences. The current study proposed a double-edged sword effect of relational crafting on job well-being, including work dynamics and emotional exhaustion, with an integrative perspective from the resource loss and resource acquisition perspectives based on the job demands-resources model and the conservation of resources theory. By conducting a two-stage questionnaire survey on 323 employees, the results demonstrate that: (1) On the one hand, relational crafting induces emotional exhaustion through increased work load; (2) On the other hand, relational crafting also displays positive effect on increasing work dynamics and decreasing emotional exhaustion by fostering supervisor-subordinate guanxi. By analyzing the double-edged sword effect of subordinates’ relational crafting on job well-being from the two processes of resource loss and resource acquisition effects, a more complete influencing mechanism between relational crafting and job well-being is constructed, which improves the understanding on relational crafting, enriches the literature on proactive behavior, and provides a more integrated theoretical basis for researchers and managers.